461 Improving specific targeting of tumors through bispecific SNIPER antibodies. (9th November 2020) - Erbe, Amy; Gerhardt, Daniel; Hernandez, Reinier; Hammer, Bonnie; Felder, Mildred; Bercher, Mark; Dennin, Jennifer; Massey, Christopher; VandenHeuvel, Sabrina; Feils, Arika; Heck, Mackenzie; Engle, Jonathan; et al.
Abstract : Background: Disialoganglioside 2 (GD2) is expressed on neuroblastomas as well as melanomas, small cell lung cancers, and sarcomas. Anti-GD2 mAb (Dinutuximab) can be used to treat these cancers and is part of the standard care for neuroblastoma. While GD2 is expressed minimally on most normal tissues, it is expressed on some nerve cells, and anti-GD2 treatment can cause neuropathic pain. A separate tumor-antigen, B7H3, is overexpressed on multiple tumor types, including those listed above, with minimal expression on most normal cells and no expression on nerve cells. We developed a bispecific SNIPER antibody, INV721, to simultaneously target these 2 tumor antigens, with one arm specific to GD2 and the other arm to B7H3. The individual Fab arms targeting GD2 and B7H3 are each low to moderate affinity, such that INV721 will only bind with high affinity when both arms bind to their antigens on the same cell, resulting in high-specificity of the SNIPER to tumor cells. Methods: INV721 binding to GD2/B7H3-expressing tumors was confirmed by flow cytometry, as well as in tumor-bearing mice injected with 89Zr-labeled to monitor in vivo biodistribution via positron emission tomography imaging. Antibody-dependent cellular cytotoxicity (ADCC) testing of INV721 was performed on human neuroblastoma and melanoma cell lines with an Incucyte spheroid-killing-assay. In vivo efficacy studies were carried out in mice bearing GD2/B7H3-expressing melanoma tumors to test our in situ vaccine (ISV) regimen, which included testing combinations of external beam radiation therapy (RT, 12Gy) ± INV721 (40 ug/dose) ± IL2 (75K U/dose). Results: INV721 showed binding by flow cytometry to tumors that express both GD2 and B7H3 but minimal binding to cells that don't express both antigens. 89Zr-INV721 showed elevated and persistent accumulation in the tumor with minimal uptake in normal tissues. Incucyte spheroid-killing assays revealed that INV721 was capable of ADCC. The ISV combination of RT+INV721+IL2 was capable of curing mice bearing 57 mm 3 melanoma tumors (12/12 mice tumor free), with >70% of these mice exhibiting long-term immune memory. Conclusions: INV721 binds to cells that express both GD2 and B7H3, and these preliminary studies show that INV721 is effective in our ISV regimen at curing mice bearing tumors that express these antigens. We are continuing our efforts to determine if INV721 is associated with less pain than Dinutuximab. The goal of this SNIPER-antibody is to enhance the tumor-specific delivery of therapeutic mAbs, which may decrease toxicity and improve efficacy for cancers expressing both GD2 and B7H3.